(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of this study is to determine the partial and simultaneous influence between personal selling and sales promotion on consumer purchasing decisions at Alfamart Mawar in Tabanan. The sample in this study was 65 people sampled using the method of determining samples using the accidental sampling method. Data collection methods are carried out by observation, interviews, and questionnaires. The data analysis technique used in this study uses multiple linear regression analysis, determination coefficient test, t test and F test. The results found in this study are 1) Personal selling has a positive and partially significant effect on purchasing decisions. 2) Sales promotion has a positive and partially significant effect on purchasing decisions. 3) Personal selling and sales promotion have a positive and significant effect simultaneously on purchasing decisions. Suggestions that can be given by researchers are employees at Alfamart Mawar in Tabanan given training, training or work patterns that are effective in attracting consumer attention so as to encourage consumers to shop at Alfamart Mawar in Tabanan and further examine other variations apart from personal selling and sales promotion variables that can influence and improve purchasing decisions.